Impact of Cold-Rolling and Heat Treatment on Mechanical Properties of Dual-Phase Treated Low Carbon Steel - Le Van Long; Dinh Van Hien; Nguyen Truong Thanh; Nguyen Chi Tho; Van Thom Do (Advances in Materials Science and Engineering)
The low carbon steel has good ductility that is favorable for forming process, but its low strength leads to limiting their application for forced structures. This paper studied improving strength of low-carbon steel via rolling deformation and dual-phase treatment. The results showed that the dual-phase treated steel had a combination of high strength and good ductility; its tensile ultimate strength reached 740 MPa with elongation at fracture of over 15%, while that of the cold-rolled steel only reached 700 MPa with elongation at fracture of under 3%. Based on the obtained results, relationships between mechanical properties and dual-phase processing parameters were established to help users choose suitable-processing parameters according to requirements of products.